Mudança do nível do mar no golfo de Cádiz durante o Plistocénico tardio e Holocénico - Boski, T. (2017)
The multiproxy information data set obtained from borehole sequences permitted to establish a robust chronology of events, which led to the post glacial infilling of the terminal stretches of regional river palleovaleys. The paleoecological reconstructions combined with 14C age model of Guadiana Estuary sedimentary record revealed the fast sea level rise period since ca 13.5 kyr cal BP, halted during the Younger Dryas and resuming at ca 11500 yr cal BP. The Holocene history of coastal evolution is also well documented in the Estuary of Arade and in Ria Formoza, pointing to the sea level stabilization at ca 7500 cal BP after a last jump of up to 8 meters in 700 years which corresponds to the Meltwater pulse 1c. Since then, the upwards movement of the sea surface continued at much slower pace, ie with the 1.2 mm yr-1 rate. The integration of the data embracing the period from since ca 13.5 ka cal BP, to the actuality enabled us to propose the sea-level rise curve for the SW Iberian Atlantic margin. When confronted with the current altimetric data from TOPEX/POSEIDON, Jason I and Jason II satellites, the millennial time-scale natural trend enables to estimate the anthropogenic forcing of SLR to be in order of 1.2 – 1.8 mm year.